Atmosphere breathing engines in astronautics - Greenwood, S. W.; Carton, D. S. (College of Aeronautics, 1958)
The contents of this note fall into two sections. Part I considers the possibilities and problems involved in using ramjets as a power source for one of the stages of a satellite launching vehicle or similar project. In comparing such a system with rocket powered vehicles, consideration is given to both performance and mass of the various systems. Various trajectories are considered. This work includes a reassessment of projects that have been suggested elsewhere. The second part examines the possibility of using forms of ramjet in the atmosphere of other planets. Because there is insufficient knowledge of these atmospheres, a study has been carried out to determine the approximate performance of a chemical ramjet in atmospheres of Methane, Ammonia, Hydrogen and Carbon Dioxide at Mach 3. The work in Part II is original, there being no previously reported papers on the subject known. These studies, which are necessarily based on several simplifying assumptions, indicate that applications for these engines may be expected to arise in astronautics, and that this is a fruitful field for further studies.